2013
DOI: 10.1176/appi.ajp.2012.11121831
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of Contingency Management for Stimulant Use in Community Mental Health Patients With Serious Mental Illness

Abstract: Objective The primary objective of this study was to determine if contingency management was associated with increased stimulant drug abstinence in community mental health outpatients with serious mental illness and stimulant dependence. Secondary objectives were to determine if contingency management was associated with reductions in use of other substances, psychiatric symptoms, HIV-risk behavior, and inpatient service utilization. Method A randomized controlled design compared outcomes of 176 outpatients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
113
2
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(128 citation statements)
references
References 45 publications
(54 reference statements)
9
113
2
3
Order By: Relevance
“…Our results, combined with recent findings on contingency management in psychiatric populations, 41 implicate the reward system as a promising approach for managing substance use in individuals with dual disorders. Future studies will need to consolidate this interpretation, as the associations we observed with cannabis use were not specific to rewarding stimuli and may indicate a more general deficit in emotional processing predicting cannabis use.…”
Section: Resultssupporting
confidence: 70%
“…Our results, combined with recent findings on contingency management in psychiatric populations, 41 implicate the reward system as a promising approach for managing substance use in individuals with dual disorders. Future studies will need to consolidate this interpretation, as the associations we observed with cannabis use were not specific to rewarding stimuli and may indicate a more general deficit in emotional processing predicting cannabis use.…”
Section: Resultssupporting
confidence: 70%
“…Bu personel tarafından, merkez bölgesinde bulunan kişilere danışmanlık, koruyucu bakım, terapi ve tedavi verilmesi ile hastaların sağlık durumlarında iyileşmelere destek sağlamaktadır. 11,[25][26][27][28][29][30][31][32][33] Ayrıca TRSM'ler hizmet alanlarında, özellikle erişim, kalite, tedavi planlamasına katılım ve iyileşme faktörlerini geliştirmek için diğer kurumlarla işbirliği yapabilirler. TRSM' ler gerekirse her bireye özel müdahale teknikleri geliştirerek birey ve toplum ruh sağlığı üzerinde koruyucu ve destekleyici etki oluşturarak toplumda genel memnuniyet düzeyini artırabilirler.…”
Section: Toplum Ruh Sağlığı Merkezlerinde Toplum Ruh Sağlığı Hemşirelunclassified
“…No obstante, tanto el grupo de asesoramiento sobre drogas como la terapia integrada de grupo muestran una aparente eficacia en el abordaje del trastorno dual 47 . El manejo de contingencias también resultó adecuado para atenuar el consumo de alcohol y estimulantes, además de para incrementar la mejoría en síntomas maníacos y depresivos 44 . Asimismo, la intervención familiar para patología dual resultó más beneficiosa en educación sobre los trastornos, sintomatología psiquiátrica y severidad de consumo que la educación familiar 45 .…”
Section: Discussionunclassified